TRAVIS SHAW’S SPEECH ACT IN THE CHOICE MOVIE SCRIPT - PAHOTAN SINAGA (JURNAL ILMIAH KOHESI, 2019)
This study aims to analyze illocutionary act used by the main characters, Travis Shaw, in a movie entitled The Choice. The objectives of this study are (1) to describe the types of illocutionary acts; (2) to find out the most dominant illocutionary acts; (3) to explain the implication of the dominance used by Travis in The Choice movie. The study uses the descriptive qualitative method to describe and analyze the selected of the illocutionary acts connect to the current context which is found in the utterances uttered by the main character, Travis, in The Choice movie. In this research, the writer finds that Travis Shaw uses all types of illoctionary act : Representatives are (36, 14%), Directives are (32, 53%), Commissives are (12, 04%), Expressives are (18, 07%), Declaratives are (1, 20%). This study reveals that the most dominant type used by Travis Shaw in his utterance of illocutionary acts of representative more often than other acts. It implies stating, describing, affirming, boasting, acknowledging, telling, reporting, speculating, claiming, boasting, mentioning, asserting and etc, in his utterances.